Etika Komunikasi Pada Media Sosial Berdasarkan Perspektif Al-Qur’an - Khairul Ikhwan Ikhwan; Wahyu , Hidayat; Wasehudin Wasehudin (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
The rise of misinformation and lies on social media is one of the unrest that occurs in society which has a negative impact on social life, this incident is because there are still many people who are not wise when using social media to communicate with fellow citizens. The purpose of this writing is to examine the ethics of communication that can be applied by social media users in accordance with the views of the Qur'an so that these social media users get many positive impacts in their lives. writing this article using the method of literature study or library research type of text book analysis. Textbook analysis is reading a number of textbooks for reference. The books used are books on interpretation, books on communication ethics, and books on social media, plus related journals. The results of this writing are obtained in using social media must follow good procedures or rules or commonly referred to as ethics. Communication ethics that are in accordance with the teachings of the Qur'an, namely Qaulan Karima (Q.S Al-Isra verse 23), Qaulan Sadida (Q.S Al-Ahzab verse 70), Qaulan Baligha (Q.S An-Nisa verse 63), Qaulan Layyinan (Q.S Thaha verse 44), Qaulan Maysiura (Q.S Al-Isra verse 28). These communication ethics must be used by social media users so that good relations are established between fellow users and bring good and keep away from bad for its users in personal life and social life. Keywords: Communication Ethics, Social Media, Al-Qur'an